John L. Sutton, The King's Honor and the King's Cardinal. The War of the Polish Succession, Kentucky 1980, s. 209 / Danuta Bogdan. - Bogdan, Danuta ([Gdańskie Towarzystwo Naukowe. Wydział I Nauk Społecznych i Humanistycznych], 1983)
Recenzja książki: The King's Honor and the King's Cardinal : the War of the Polish Succession / John L. Sutton. Kentucky, 1980.